1997
DOI: 10.1161/01.atv.17.11.2622
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived Growth Factor β-Receptors Can Both Promote and Inhibit Chemotaxis in Human Vascular Smooth Muscle Cells

Abstract: The effect of the three platelet-derived growth factor (PDGF) isoforms AA, AB, and BB on migration was investigated in cultured human saphenous vein smooth muscle cells. The modified Boyden chamber technique yielded efficacies BB >> AB, AA = 0. However, the BB concentration-response relationship displayed a pronounced peak, occurring between 1 and 10 ng/mL, with no response above this range. Checkerboard analysis showed that the promotion of migration at low concentrations was chemotactic in nature but that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
28
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 19 publications
6
28
0
Order By: Relevance
“…37 In fact, when either bFGF binding to its receptor or PDGF-R␣ signaling was impaired, the inhibitory effect of bFGF was abolished. This finding is in agreement with the known modulating role of PDGF-R␣ [38][39][40] and was further confirmed by a recent report indicating that PDGF-R␣ activates JNK-1 signaling, counteracting PDGF-R␤ activity. 41 Therefore, we have hypothesized that PDGF may inhibit bFGF-induced angiogenesis, and we have, in the current study, determined whether PDGF modulates bFGF activity on ECs in vitro and in vivo.…”
Section: Introductionsupporting
confidence: 92%
“…37 In fact, when either bFGF binding to its receptor or PDGF-R␣ signaling was impaired, the inhibitory effect of bFGF was abolished. This finding is in agreement with the known modulating role of PDGF-R␣ [38][39][40] and was further confirmed by a recent report indicating that PDGF-R␣ activates JNK-1 signaling, counteracting PDGF-R␤ activity. 41 Therefore, we have hypothesized that PDGF may inhibit bFGF-induced angiogenesis, and we have, in the current study, determined whether PDGF modulates bFGF activity on ECs in vitro and in vivo.…”
Section: Introductionsupporting
confidence: 92%
“…23 In brief, the upper and lower compartments of the blind-well chambers were separated by gelatin-coated polycarbonate filters. TSP-1 (10 g/mL) was added to the lower chamber and acted as the chemoattractant.…”
Section: Cell Migration Assaysmentioning
confidence: 99%
“…7). In a previous report on saphenous vein-derived VSMC, PDGF-BB was reported to have a biphasic effect on PDGF-βR level and chemotaxis, but the pathways involved were not identified and the ambient glucose level not given [14].…”
Section: Discussionmentioning
confidence: 95%
“…It has been suggested that the chemoattractant effect on VSMC (saphenous vein-derived) is lost at high PDGF-BB concentrations (glucose concentration not stated) [14]. The activation state of signalling pathways depends on the balance between phosphorylation and dephosphorylation of key molecules.…”
Section: Introductionmentioning
confidence: 99%